A Description of the Character, Manners and Customs of the People of India and of their Institutions, Religious and Civil - Dubois, Abbé J.A., (Brill | Manohar Publishers & Distributors, 2023)
First published in 1879, A Description of the Character, Manners and Customs of the People of India and of their Institutions, Religious and Civil by the Abbé J.A. Dubois, and translated from French by Rev. G.U. Pope, is arranged into three parts, with each section devoted to various aspects and society of the Indian people who lived in south India of that time. The author, Abbé J.A. Dubois, who was a French missionary, states at the outset that his work is the result of a period of almost eighteen years when he lived amongst the Indian people just the way they did, adopting the indigenous forms of living and clothing - even their prejudices. Thus, he not only familiarized himself with their lifestyle, but also won their confidence which helped him in writing of this book. Thus, his study is based on first-hand experience. For convenience of the readers, the editor's footnotes that provide explanations as well as references and cross-references to Indian scriptures and other texts have contributed to the value of this work. Part I studies the caste system, with its divisions and subdivisions, its origins, and prayers, ceremonies, and beyond. Part II, devoted to Brahmins, examines in detail the four stages of life, the norms and practices that govern them, discussing defilements and remedies, rules governing Brahmin women, Hindu philosophers and many others. Part III focuses on religion and includes the Trimurti, festivals, animal worship, Jains, military system, etc.